Perceived Working Conditions and Intention to Adopt Digital Safety Training in High-Risk Productive Sectors: An Exploratory Study in Manufacturing and Agriculture in Northwest Italy - Francesco Sguaizer; Lucia Vigoroso; Margherita Micheletti Cremasco; Federica Caffaro (Safety)
Agriculture and manufacturing report the highest rate of occupational accidents and fatalities in Italy. Safety training provided through digital devices has been shown to be effective in promoting safety behaviors at work. This study aimed to investigate through a questionnaire the perceptions of working conditions, risks in using machines, and interest in using digital devices for safety training purposes in a group of vineyard workers (VWs, N = 40) and manufacturing workers (MWs, N = 39) in Northwest Italy. Referring to working conditions, VWs significantly differ compared to MWs (p < 0.05) in fatigue perception, repetitiveness, quantity and definition of tasks compared to the available time, work pace definition, and level of communication. Tractors and lathes were considered the most hazardous machinery for VWs and MWs, respectively. For both groups, workers’ age negatively correlated with digital device use (r = −0.399 p < 0.05 for VWs, r = −0.673 p < 0.01 for MWs) but not with interest in using them. Device adoption positively correlated with the perceived importance of gamification content (r = 0.193 and r = 0.164, p > 0.05 for VWs and MWs, respectively), but the video lessons reported a higher mean score by both groups as preferred content. These findings suggest that digital safety training requires customized content to effectively adapt to different productive sectors.